Mucosal-Associated Invariant T Cells Display Diminished Effector Capacity in Oesophageal Adenocarcinoma - Melo, Ashanty M.; O'Brien, Aisling M.; Phelan, James J.; Kennedy, Susan A.; Wood, Nicole A. W.; Veerapen, Natacha; Besra, Gurdyal S.; Clarke, Niamh E.; Foley, Emma K.; Ravi, Akshaya; MacCarthy, Finbar; O'Toole, Dermot; et al. (Frontiers in Immunology, 2019)
Oesophageal adenocarcinoma (OAC) is an aggressive malignancy with poor prognosis, and incidence is increasing rapidly in the Western world. Mucosal-associated invariant T (MAIT) cells recognise bacterial metabolites and kill infected cells, yet their role in OAC is unknown. We aimed to elucidate the role of MAIT cells during cancer development by characterising the frequency, phenotype and function of MAIT cells in human blood and tissues, from OAC and its pre-malignant inflammatory condition Barrett’s oesophagus (BO). Blood and tissues were phenotyped by flow cytometry and conditioned media from explanted tissue was used to model the effects of the tumour microenvironment on MAIT cell function. Associations were assessed between MAIT cell frequency, circulating inflammatory markers, and clinical parameters to elucidate the role of MAIT cells in inflammation driven cancer. MAIT cells were significantly decreased in BO and OAC blood compared to healthy controls, but were increased in oesophageal tissues, compared to BO-adjacent tissue, and remained detectable after neo-adjuvant treatment. MAIT cells in tumours expressed CD8, PD-1 and NKG2A but significantly lower NKG2D. MAIT cells produced significantly less IFN-γ and TNF-α in the presence of tumour-conditioned media. OAC cell line viability was significantly reduced upon exposure to MAIT cell lines. Serum levels of chemokine IP-10 were strongly inversely correlated with MAIT cell frequency in both tumours and blood. MAIT cells were significantly higher in the tumours of node-negative patients, but were not significantly associated with other clinical parameters. This study demonstrates that OAC tumours are infiltrated by MAIT cells, a type of CD8 T cell featuring immune checkpoint expression and cytotoxic potential. These findings may have implications for guiding future immunotherapy and immune scoring approaches.